(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Law is only juridical science. Each sector must have a legal body overseeing the individual zone’s functions and directing it. India being one of the quickest developing economies has the third biggest energy shoppers in the world with an incredible potential to make sustainable power source yet it comes up short on a sound law for Renewable Energy Sector. India has exceptional climatic conditions which bolster sustainable power source creation as well as lift energy security in India. The energy utilization pace is expanding at a more prominent rate in India. About 70 of India’s power age limit is from Fossil fuels in this way India is to a great extent subject to fossil fuels to fulfill its energy needs. In spite of the fact that being to a great extent subject to fossil fuels India is currently breaking the generalizations in the energy sector by giving driving force on sustainable power source creation. The demand for power is expanding because of accentuation on economic development, improved way of life and Government duty to give power to all by 2022. By and by, greatest bit of demand is met through conventional energy in any case, because of environmental change issues, practical improvement, government pledge to lessen the energy force of GDP and inexhaustible power (RE) assets ending up financially accessible everywhere scale has prompted accentuation on advancement of sustainable power source. In this Research Study we learned about the different Drawbacks and Regulatory Frameworks, Policies in regards to Renewable Resources.